Розвиток інноваційної і сталої інфраструктури: досвід Європейського Союзу - Яншина, А. М. (Видавництво Львівської політехніки, 2015)
Проаналізовано сучасні наукові підходи до дослідження проблем створення інноваційної інфраструктури у країнах світу у контексті сталого зростання як найсуттєвішого аттрактора розвитку міжнародної економіки. Розкрито ключові тенденції й особливості формування інноваційної і сталої інфраструктури на наднаціональному і національному рівнях у межах Європейського союзу. Запропоновано рекомендації щодо формування інноваційної і сталої інфраструктури в Україні в умовах її інтеграції до Європейського союзу. A drastic deterioration in environmental performance of developed countries as well as emerging markets triggered off by devastating resource usage, environmentally and socially intolerant economic behavior has turned national-level goal of greening and socializing economic growth into a worldwide challenge of utmost importance. Innovative and sustainable infrastructure plays a pivotal role in the sustainable development concept implementation at all levels. In the article academic approaches to the innovative infrastructure are examined in the light of sustainable development as a key world economy attractor. The author investigates latest trends and features of the EU infrastructure modernization. The infrastructure performance of the EU Member-States has been rather strong and innovative of late but not permanently sustainable. Thus amongst many terms used to outline a final and expected result of infrastructure renovation – sustainable, innovative, green infrastructure – the last one aimed at ensuring eco-friendly economic effects as well as non-environmental benefits is supposed to be the most applicable to the modern EU context. Green infrastructure goals have been incorporated into all main supranational policy frameworks of the European Union since Green Infrastructure Strategy «Green Infrastructure – Enhancing Europe’s Natural Capital» was adopted in May 2013. To meet decarbonization challenges and integrate new Member-States into intra-EU economic affairs the European Union prioritize greening energy and transport infrastructure. Active civil society dialogue on green infrastructure issues is ensured by a variety of NGOs represented at all EU levels and via a number of on-line platforms. France, Germany, Austria, Belgium and Finland are the EU leaders in terms of innovative infrastructure. However the world economic crisis has negatively impacted the infrastructure financing. After the World War II the public sector was a key investor in infrastructure across Europe. Nowadays public sector investments in infrastructure have dropped, the total number of public-private projects is low as well.
Innovative and sustainable infrastracture development: best EU practices
Keywords: сталий розвиток; інновація; зелена інфраструктура; навколишнє середовище; Європейський союз; sustainable development; innovation; green infrastructure; environment; European Union